2023
DOI: 10.3390/toxics11020159
|View full text |Cite
|
Sign up to set email alerts
|

Hypericum perforatum L. Nanoemulsion Mitigates Cisplatin-Induced Chemobrain via Reducing Neurobehavioral Alterations, Oxidative Stress, Neuroinflammation, and Apoptosis in Adult Rats

Abstract: Cisplatin (Cis) is a potent chemotherapeutic agent; however, it is linked with oxidative stress, inflammation, and apoptosis, which may harmfully affect the brain. Hypericum perforatum L. (HP L.) is a strong medicinal plant, but its hydrophobic polyphenolic compounds limit its activity. Therefore, our study aimed to investigate the neuroprotective action of HP L. and its nanoemulsion (NE) against Cis-induced neurotoxicity. The prepared HP.NE was subjected to characterization. The droplet size distribution, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…As is known, 8‐OHdG is one of the most important biomarkers of oxidative stress and is an important indicator used in the determination of DNA damage 49 . Khalil et al., 50 reported that 8‐OHdG levels were increased and the degree of DNA damage was increased in the CIS group. Similarly, Mansour et al., reported that 8‐OHdG levels increased in the brain tissues of CIS‐treated rats and this was associated with the increase in ROS production caused by CIS and acceleration of oxidative DNA damage 51 .…”
Section: Discussionmentioning
confidence: 99%
“…As is known, 8‐OHdG is one of the most important biomarkers of oxidative stress and is an important indicator used in the determination of DNA damage 49 . Khalil et al., 50 reported that 8‐OHdG levels were increased and the degree of DNA damage was increased in the CIS group. Similarly, Mansour et al., reported that 8‐OHdG levels increased in the brain tissues of CIS‐treated rats and this was associated with the increase in ROS production caused by CIS and acceleration of oxidative DNA damage 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the tested compound was able to diminish cisplatin-induced cortical toxicity via multiple signaling pathways, lowering the behavioral changes, inflammation response, and levels of oxidative stress. Another study conducted on Wistar albino rats tested the effects of nanoemulsion formed with Hypericum perforatum L. extract on cisplatin-induced cognitive impairment, a state often caused by most chemotherapeutics [82]. After the administration of Hypericum nanoemulsion for 21 days, the toxicity in animals was induced by a single dose of cisplatin (10 mg/kg, i.p.).…”
Section: Overview Of Recent Relevant Animal Modelsmentioning
confidence: 99%
“…Para a seleção de artigos foram utilizados os quatro elementos da estratégia PICO, uma metodologia para nortear a pesquisa (SANTOS et al 2007) (TABELA 1). Foram incluídos artigos em inglês, publicados no período de 5 anos (2018)(2019)(2020)(2021)(2022)(2023). Os artigos selecionados foram do tipo intervencional (experimentais), que utilizaram ratos apenas da linhagem Wistar, para melhor comparação entre apenas uma mesma linhagem de rato.…”
unclassified